Peningkatan Nilai Tambah Ampas Tahu Menjadi Tempe Gembus Pada Pabrik Tahu Pak Sugeng - Damarsiwi, Eska Monique; Putri, Indi Desti Dwi (Jurnal Dehasen Mengabdi, 2023)
Tofu dregs are solid waste obtained from the process of making tofu from soybeans. in this training there are several stages carried out in the processing of tofu dregs into tempe gembus: the first stage carried out in the trainer is to recognize what are the benefits or other uses of tofu dregs that can be processed into tempe gembus. the second stage carried out in the training is to introduce what materials and tools are used to make processed tofu dregs into tempeh gembus. The second stage carried out in the training is to introduce what materials and tools are used to make processed tofu dregs into tempe gembus. the third stage carried out in the study is other benefits of tofu dregs that can be used to make tempe gembus with easy and practical materials. tempe gembus is marketed at a low price this is likely because tempe gembus is the result of waste processing which is considered to be of low quality because the community considers low quality tempe gembus has no nutritional value, it is necessary to process it to add value to tempe gembus by adding the enzyme bromelain so that the tempe gembus protein is more easily digested.